Penguatan Kesadaran tentang Kebersihan di Pasar Tradisional Sukaramai Teluk Belitung Kabupaten Kepulauan Meranti - Chaidir, Kholid; Islah, Andari Putri (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2023)
The purpose of this service is: 1) to raise awareness of citizens to keep the environment clean and not to litter considering the dangers caused by littering; 2) the community does not throw garbage in ditches or waterways; and 3) apply some sort of social punishment if someone litters. The techniques used in finding problems in this community service activity are the Direct Observation and Semi Structured Interviewing techniques. Direct Observation, namely the activity of direct observation of certain objects, events, processes, public relations, and equipped with pictures or photographs which are used as evidence that have a certain meaning in accordance with the actual situation. While semi-structured interviews are a data collection technique that uses systematic guidelines which are only open guidelines and are still possible to develop during the interviews. Semi-structured interviews can be conducted with individuals who are considered to represent information, women, men, children, people who are considered to have certain knowledge where other people do not have that knowledge, for example farmers, health workers. It can also be done by groups in order to obtain information from all levels of society. The results of the activities achieved were: 1) the emergence of awareness when disposing of waste in its place, there were calls or warnings from people who saw it so as to create a clean environment and avoid waste; 2) saving land for landfills. The benefits of effective waste management so that waste that has a function such as used bottles can be used as flowers or something else; 3) the environment is clean and comfortable, waste management is effective and the environment is protected from garbage just lying around, all garbage is placed according to its designation.